2013
DOI: 10.1055/s-0033-1333717
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor mRNA Measured by Quantitative Real Time PCR is Decreased in the Urethral Mucosa of Patients with Middle Idiopathic Hypospadias

Abstract: Androgen action is exerted through the androgen receptor. The normal 46,XY genital virilization depends on androgen receptor gene expression, which is tissue specific, and requires normal androgen receptor mRNA levels in androgen sensitive tissues. Hypospadias is a frequent male genital abnormality, potentially related to reduced androgen sensitivity in genital tissues. The aim of this study was to compare, by quantitative real time PCR, the amount of androgen receptor mRNA in cells obtained from the urethral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Later clinical studies support this. The results of these studies demonstrated that AR expression had decreased in both foreskin and urethral mucosa samples taken from patients with hypospadias [Goyal et al, 2007;Silva et al, 2013]. But, Pichler et al [2013] detected increased AR mRNA levels in prepuce samples from patients with hypospadias and evaluated compensatory upregulation at the receptor, decreased AR DNA binding capacity, and AR signal defects.…”
Section: Discussionmentioning
confidence: 99%
“…Later clinical studies support this. The results of these studies demonstrated that AR expression had decreased in both foreskin and urethral mucosa samples taken from patients with hypospadias [Goyal et al, 2007;Silva et al, 2013]. But, Pichler et al [2013] detected increased AR mRNA levels in prepuce samples from patients with hypospadias and evaluated compensatory upregulation at the receptor, decreased AR DNA binding capacity, and AR signal defects.…”
Section: Discussionmentioning
confidence: 99%
“…The human AR gene, also known as the dihydrotestosterone receptor, is located on X-chromosome and a member of the nuclear hormone receptor family. Although AR defect may play a causative role during the development of hypospadias, the AR expression (Balaji et al, 2020;Celayir et al, 2019;Lin et al, 2016;Pichler et al, 2013;Silva et al, 2013;Tack et al, 2019) in hypospadias is still debatable. Lin et al (2016) and Silva et al (2013) reported the decreased AR expression in boys with hypospadias compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs identified associated with increased risk [33,36,37]. No significant haplotype association [23].…”
Section: Esr2mentioning
confidence: 97%